Conditions Of Scleractinian Coral Cover Percentage On The North Coast Of Ambon Island, Maluku Province - Muhammad Fahrul Barcinta; Masudin Sangaji; Gino V. Limmon (International Journal of Science and Environment (IJSE), 2023)
Coral reefs are one of the most ecologically productive and diverse ecosystems. This study aims to determine the condition of scleractinian coral cover in the northern coastal waters of Ambon Island. Data collection in the field is carried out using the systematic sampling method. A quadrant measuring 1x1 m2 becomes the sampling area. Quadrants are placed on transects 20 m long with quadrant intervals on transect lines of 5 m (0, 5, 10, 15, and 20 m). The transects are placed parallel to the shoreline at depths of 3 m and 10 m, with four transects at each depth, and the distance between transects is 1 m. The data obtained were then analyzed to see the percentage of coral cover in each category and component. The results showed that the percentage of the benthic substrate of coral reefs on the North Coast of Ambon Island to a depth of 3 meters was dominated by rubble with a percentage of 26.33% - 54.83%, and for a depth of 10 meters the percentage value of ruble was 11.33% - 48.83% and sand (4% - 54.50%). The category of Acropora corals both at a depth of 3 meters and 10 meters dominated by Acropora branching (ACB), while the non-acropora category is dominated by Coral Branching (CB), Coral Encrusting (CE), and Coral Massive (CM). Overall, the condition of live coral cover on the North Coast of Ambon Island is categorized as in poor condition.